Clinical utility of a 1.5 T magnetic resonance imaging-guided linear accelerator during conventionally fractionated and hypofractionated prostate cancer radiotherapy - Turkkan, Gorkem; Bilici, Nazli; Sertel, Huseyin; Keskus, Yavuz; Alkaya, Sercan; Tavli, Busra; Ozkirim, Muge; Fayda, Merdan (Frontiers in Oncology, 2022)
Purpose: To report our initial experience with 1.5 T magnetic resonance imaging (MRI) linear accelerator (LINAC) in prostate cancer radiotherapy in terms of its use in a radiation oncology clinic. Methods: The medical records of 14 prostate cancer patients treated with MRI-guided radiotherapy were retrospectively evaluated. The fraction time, adapt-to-position (ATP):adapt-to-shape (ATS) usage rate, machine-associated treatment interruption rate, median gamma pass rate, the percentage of planning target volume receiving at least 95% of the prescription dose coverage value of each ATS fraction, the effect of the learning curve on the fraction time and radiation-related acute gastrointestinal and genitourinary toxicities were evaluated. Results: Fourteen patients have completed their treatment receiving a total of 375 fractions. Six patients (42%) were treated with the moderately hypofractionated regimen, five patients (36%) with conventionally fractionated, and three patients (22%) with the ultra-hypofractionated radiotherapy regimens. The ATP:ATS usage ratio was 3:372. The median fraction time was 46 min (range, 24-81 min). For the 3%/3 mm criterion, median gamma pass rate was 99.4% (range, 94.6–100%). Machine-related treatment interruptions were observed in 11 (2.9%) of 375 fractions, but this interruption rate decreased from 4.1% to 0.8%, after an upgrade. Three patients (2%) had gastrointestinal and five patients (36%) had genitourinary toxicity. No ≥grade 3 toxicity was observed. Conclusion: 1.5 T MRI-LINAC device could be used as a conventional LINAC device, when the conditions of the radiotherapy center are appropriate. MRI-guided prostate radiotherapy is safe and feasible, and high-quality studies with a larger number of patients and long-term results are needed to better evaluate this new technology.